Unveiling and veiling an entangled light-matter quantum state from the vacuum - Roberto Stassi; Mauro Cirio; Ken Funo; Jorge Puebla; Neill Lambert; Franco Nori (Physical Review Research, 2023)
The ground state of an atom interacting with the electromagnetic field in the ultrastrong coupling regime is composed of virtual photons entangled with the atom. We propose a method to promote to real the entire photonic state, while preserving the entanglement with the atom. The process can be reversed, and the entangled state can be restored in the vacuum. We consider a four-level atom, with two of these levels ultrastrongly coupled to a cavity mode. The process is obtained by making use of either an ideal ultrafast pulse or a more realistic multitone π pulse that drives only the atom. An experimental realization of this proposal will not only enable the investigation of the exotic phenomena of emission of particles from the vacuum, but will also prove that quantum superposition states can be extracted from the vacuum. Moreover, it will allow one to inspect the ground state in the ultrastrong coupling regime, and to generate on-demand entangled states for quantum information processing.